1979
DOI: 10.2135/cropsci1979.0011183x001900040011x
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis and Ploidy Effects on the Growth of Alfalfa Callus1

Abstract: The influence of heterosis and ploidy level on callus fresh weight production in alfalfa (Medicago sativa L.) was studied using diploids (2x), their isogenic tetraploid (4xCD) counterparts derived by chromosome doubling, hybrids at 2x and 4x levels, and 4x and isogenlc 8xCD materials Chromosome doubling has an inbreeding fect equivalento sewing (2 to 3 generations in 4x), thus 4xCD and 8xCD materials were partial inbreds. Both the 4xCD and 8xCD materials produced less callus than their non‐inbred 2x and 4x cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1

Year Published

1982
1982
1997
1997

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 0 publications
1
8
1
Order By: Relevance
“…Although the present study failed to detect significant positive heterosis it has previously been reported for callus growth in alfalfa (Keyes and Bingham, 1979) and in Nicotiana (Keyes et a!., 1981). it has been recommended that hybrid vigour exhibited in cell and tissue culture may be of value in the identification of heterokaryons following somatic fusion.…”
Section: Discussioncontrasting
confidence: 63%
“…Although the present study failed to detect significant positive heterosis it has previously been reported for callus growth in alfalfa (Keyes and Bingham, 1979) and in Nicotiana (Keyes et a!., 1981). it has been recommended that hybrid vigour exhibited in cell and tissue culture may be of value in the identification of heterokaryons following somatic fusion.…”
Section: Discussioncontrasting
confidence: 63%
“…A summary of much of the literature in this area has been provided by Keyes and Bingham (1978). From this it is clear that many characteristics of plant tissue culture are under specific genetic control.…”
Section: Discussionmentioning
confidence: 99%
“…Inbreeding via either chromosome doubling or conventional selfing reduces in vitro callus production (Keyes and Bingham 1979 …”
Section: Mots Clésmentioning
confidence: 99%
“…Angus cotyledons. Wide variations for callus growth among genotypes within some cultivars were also detected.Inbreeding via either chromosome doubling or conventional selfing reduces in vitro callus production (Keyes and Bingham 1979 …”
mentioning
confidence: 99%
See 1 more Smart Citation